TOWARDS SUSTAINABLE SOCIETIES - Nandhikkara, Jose (Journal of Dharma, 2021)
The Journal of Dharma volume 46 (2021) investigates human quest ‘Towards Sustainable Societies’ and explores the Ethical interface of Sustainable Development Goals and the roles of educational, economic, political, legal, and religious policies, systems, and institutions, bringing together research from different academic fields including Literature, Media, Environmental Sciences, Law, Economics, Philosophy, and Religious studies. Vol. 46.1. focus on “Towards Sustainable Societies: People, Ethics, and Development.” In the Preamble of the SDG Agenda, we read: “We are determined to end poverty and hunger, in all their forms and dimensions, and to ensure that all human beings can fulfil their potential in dignity and equality and in a healthy environment.” People are the focus of the SDG, especially the first five goals in the Agenda.